High rate of colistin resistance among patients with carbapenem‐resistant Klebsiella pneumoniae infection accounts for an excess of mortality. (9th November 2012) - Capone, A.; Giannella, M.; Fortini, D.; Giordano, A.; Meledandri, M.; Ballardini, M.; Venditti, M.; Bordi, E.; Capozzi, D.; Balice, M. P.; Tarasi, A.; Parisi, G.; et al.
Abstract Carbapenem‐resistant Klebsiella pneumoniae (CR‐KP) is becoming a common cause of healthcare‐associated infection in Italy, with high morbidity and mortality. Prevalent CR‐KP clones and resistance mechanisms vary between regions and over time. Therapeutic approaches and their impact on mortality have to be investigated. We performed a prospective study of patients with CR‐KP isolation, hospitalized in nine hospitals of Rome, Italy, from December 2010 to May 2011, to describe the molecular epidemiology, antibiotic treatment and risk factors for mortality. Overall, 97 patients (60% male, median age 69 years) were enrolled. Strains producing blaKPC‐3 were identified in 89 patients, blaVIM in three patients and blaCTX‐M‐15 plus porin defects in the remaining five patients. Inter‐hospital spread of two major clones, ST512 and ST258, was found. Overall, 36.1% and 20.4% of strains were also resistant to colistin and tigecycline, respectively. Infection was diagnosed in 91 patients who received appropriate antibiotic treatment, combination therapy and removal of the infectious source in 73.6%, 59.3% and 28.5% of cases, respectively. Overall, 23 different antibiotic regimens were prescribed. In‐hospital mortality was 25.8%. Multivariate analysis adjusted for appropriate treatment, combination therapy and infectious‐source removal, showed that Charlson comorbidity score, intensive‐care unit onset of infection, bacteraemia and infection due to a colistin‐resistant CR‐KP strain were independent risk factors for mortality. The spread of clones producing K. pneumoniae carbapenemases, mainly ST258, is currently the major cause of CR‐KP infection in central Italy. We observed a high rate of resistance to colistin that is independently associated with worse outcome.